Study of Anaemia in Children with Severe Acute Malnutrition - Dwivedi, Deepak; Singh, Veerendra; Singh, Jyoti; Sharma, Sangita (Journal of Nepal Paediatric Society, 2018)
Introduction: Severe anaemia is a leading cause of paediatric morbidity, hospitalization, and mortality and it is very important co morbidity in children with severe acute malnutrition. Severe Acute Malnutrition (SAM) with anaemia has been shown to have 2.62 times higher mortality as compared to SAM with no anaemia. So this study was done to evaluate this co-morbidity further. The aim of present study was to determine the prevalence and type of anaemia and to evaluate the possible aetiologies of anaemia in severe acute malnourished (SAM) children. Material and Methods: In tertiary care hospital a cross sectional study was conducted over a period of 8 month with 100 cases of SAM children and 101 cases of normal children. In both cases disorders of primary haematological problem were excluded. Auto analysers were used to measure blood counts. Blood smear was analysed by pathology consultant of institute and recorded for all patients with anaemia. Grade of anaemia and morphologic type of anaemia was analysed. Data were entered in Excel spreadsheets and analysed using SPSS 20.0. Results: Patient with SAM 42% had moderate anaemia and 19% had severe anaemia in contrast 41.6% and 16.8% in NON SAM child respectively. Predominant morphologic type in SAM patient was macrocytic anaemia (33%), while in controls microcytic anaemia (40.6%) was more prevalent. Conclusion: There was a high prevalence of anaemia in SAM children. Major morphologic type in SAM children was macrocytic anaemia which may indirectly show vitamin B12 or folic acid deficiency in these children.